AB0075 The endogenous angiostatic mediators endostatin and thrombospondin-1 are increased in psoriatic arthritis. (23rd January 2014) - Delle Sedie, A.; Puxeddu, I.; Tronchetti, M.; Migliorini, P.; Bombardieri, S.; Riente, L.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory joint disease associated with psoriasis, classified within the familyof spondyloarthropathies. The events underlying the pathogenesis of PsA have not yet been fully elucidated. It is known that angiogenesis is an early event in the joint inflammation during PsA, resulting in cartilage degradation and bone destruction. Previous studies have demonstrated an increase of circulating pro-angiogenic mediators, including vascular endothelial growth factor (VEGF) in PsA. The role of endogenous inhibitors of angiogenesis in PsA is unknown. Objectives: The aim of our study is to investigate the potential involvement of Endostatin (ES) and Thrombospondin-1 (TSP-1), extracellular matrix (ECM) fragments with anti-angiogenic activity, in patients with PsA. Methods: Fifty four adult patients with PsA were studied. The diagnosis of PsA was established according to the CASPAR criteria. Endostatin (ES) and Thrombospondin-1 (TSP-1) were measured, by enzyme immunoassays, in the sera of these patients and of 52 patients with Rheumatoid Arthritis (RA), diagnosed according to the 2010 ACR-EULAR classification criteria, and of 39 healthy subjects. Results: The serum level of ES resulted significantly higher in the PsA group than in the control subjects (P<0.0001), similarly to that detected in RA. Parallel to ES, TSP-1 levels were significantly higher in PsA (P<0.0001) compared to the controls and significantly higher than RA (P=0.0003). Conclusions: The observed increase of ECM fragments with anti-angiogenic properties suggests a reduction of pro-angiogenic activity in PsA. It is possible that this reduction is due to underlying treatments. Disclosure of Interest: None Declared